Configuración del Turismo en el ambiente globalizado. Estudio de casos de Clusters turísticos - Toledo, Geraldo Luciano; Valdés, Jesús Álvarez; Pollero, Álvaro Castroman (Revista Turismo em Análise, 2002)
The strategy of lhe tourist companies is perfected to reach the competitiveness by lhe cooperative arrangements in clusters. This paper will present a theoretical reference model to analyze the dimensions of the competitiveness. A tourist cluster reaches your competitive positioning if its companies implement competitives, cooperatives and relationships strategies. The model is examined by case studies. The tourist clusters of the south of Australia, Costa Rica and northeasl of Brazil are appraised with this methodology.